2020
DOI: 10.1136/bmj.m520
|View full text |Cite
|
Sign up to set email alerts
|

Computerised speech and language therapy can help people with aphasia find words following a stroke

Abstract: The study Palmer R, Dimairo M, Cooper C, et al. Self-managed, computerised speech and language therapy for patients with chronic aphasia post-stroke compared with usual care or attention control (Big CACTUS): a multicentre, single-blinded, randomised controlled trial. Lancet Neurol 2019;18:821-33. This project was funded by the NIHR Health Technology Assessment Programme (project number 12/21/01) and the Tavistock Trust for Aphasia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The commonly used interventions in treating aphasia focused on promoting the plasticity of the remaining brain 23 , including SLT 7,24 , noninvasive brain stimulation such as transcranial stimulation 25 . The effects of these methods were reported to be beneficial, but further improvement was still needed [26][27][28] . As these interventions could vigor the compensational network for the language function, combining these methods with the CC7 nerve transfer or a simplified surgery is promising 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The commonly used interventions in treating aphasia focused on promoting the plasticity of the remaining brain 23 , including SLT 7,24 , noninvasive brain stimulation such as transcranial stimulation 25 . The effects of these methods were reported to be beneficial, but further improvement was still needed [26][27][28] . As these interventions could vigor the compensational network for the language function, combining these methods with the CC7 nerve transfer or a simplified surgery is promising 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Aphasia is the most common sequela in stroke patients. About one-third of stroke survivors suffer from aphasia ( 8 , 9 ), which persists in approximately 30–43% of these patients ( 10 ). Non-fluent aphasia is one of the most common types of aphasia, presenting as damage to the speech center in the left hemisphere ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an increasing number of studies have focused on the use of mobile applications, such as computers and tablets, to enhance the expressive language skills of individuals with aphasia ( 9 , 10 ). For example, Zhou et al ( 11 ) found that a 14-day, 30-min-a-day computer-based training session resulted in more significant speech improvements compared to traditional treatments.…”
Section: Introductionmentioning
confidence: 99%